A Study for External Facade Cleaning Using Rope Access Equipment: Hazard Identification and Risk Assessment - Sarah Aqilah Ahamad Nazeer,; Nurrul Hafeezah Sahak,; Suhairul Nizam Jahidin, (Progress in Engineering Application and Technology, 2024)
Modern buildings' facades require regular facade cleaning to identified and addressed damage, extended structure life, and reduce costly repairs.  Rope access window cleaning had a lowered accident risk due to improved technology and competence.  Even though it had an excellent safety reputation, rope-access window washing had received its fair shared of attention throughout the years.  The objective of this studied was to determine the leveled of risk involving facade cleaning used rope, used hazard identification, risk assessment, and risk controlled (hirarc) to identified potential hazards such as fell, dangerous equipment, suspension rigging, and anchor pointed conditions.  The studied utilized both primary and secondary data collection methods, including field observation, and checklists that were focus group discussions with experts and team facade cleaning.  This researched used the hazard identification, risk assessment, and risk controlled (hirarc) method.  The results indicated that the risk assessment during filling identified three high-risk hazards which were strong winds over 25 knots, working at high placed, and emergencies working in a suspended situation.  This researched needed controlled measures to minimize workplace accidents in the facade cleaning process by eliminating, administrative controlled and used of ppe (personal protective equipment)